ANALISIS PERENCANAAN KEBUTUHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (Studi Pada Kantor Perwakilan BKKBN Provinsi Nusa Tenggara Barat ) - winarti winarti; Agusdin agusdin; hermanto hermanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at analyzing the work load and the need of human resources development in the provincial office of Population and Family Planning Agency of West NusaTenggara. This research is descriptive-qualitative study supported by qualitative data. The data were analyzed with Workload Indicator of Staffing Needs (WISN) and Force-Field Analysis (FFA). The samples were 72 respondents selected from 94 populations. With the WISN analysis, the research showed that there is different workload of each unit; 4 units are lack of human resources and 2 other units are surplus of human resources, and 1 unit had sufficient workload and human resources. With the FFA analysis of human resources development, the research showed that formal education, trainings, and workshops were needed to upgrade the knowledge and skills in equipment and drug for contraception, public speaking, partnership and information technology. This research recommended that authority do mutation, take outsourcing, and make partnership to balance the workload in each unit and develop human resources by making policy in terms of education, trainings, and workshop that support the job description.Keywords: workload, WISN, FFA, Human resources development.